Tolerance is an enlightening Islamic vision –majed al-gharbawi is a model: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Imene ameur, Dr; Dounia Messaoud khalouf, Dr. (lark, 2022)
Like love , peace, tolerance is a human virtue in the first place, before any religious or social instituation, it is a necessity with which we meet the values of intolerance, violence and preparedness that have destroyed humanity, locke and Voltaire wrote their letters in tolerance of the necessity and spread of all forms of violence in the absence of tolerance, calling for the acceptance of the other. Many have called for it, whether in the arab or western world, one of the most important advocates of the value of tolerance in the arab world is “majed al-gharbawi” who presented a purely rational and philosophical vision to create a new paradigm of tolerance that deconstructs intolerance, from the reality of the Islamic environment, which witnessed extremism and tyranny, given the lack of awareness among peoples and the lack of proper understanding of the quranic text, it is necessary to cooperate to dismantle the extremist system and replace it with positive values, so that tolerance,love and solidarity prevail throughout the Islamic world at a time when violence in the name of religion has spread.